2021
DOI: 10.1007/s00520-021-06166-0
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based interventions for breast cancer patients in China across outcome domains: a systematic review and meta-analysis of the Chinese literature

Abstract: Objective This study aims to evaluate the treatment effect of a mindfulness-based intervention for Chinese breast cancer patients across outcome domains, including symptom-related, psychosocial, and quality of life outcomes. Methods Following the Cochrane Systematic Review guideline, we searched across five electronic databases, reference lists of eligible studies, professional websites, and major academic journals in Chinese. Publication bias was assessed using funnel plot and Vevea and Woods sensitivity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The use of adjuvant therapies based on behavioral or psychological interventions, such as music therapy, mindfulness, RE: estrogen receptor; HER2: human epidermal growth factor receptor type 2; RE: estrogen receptor; HER2: human epidermal growth factor receptor type 2; *doxorubicin (60 mg/m²) and cyclophosphamide (600 mg/m²), every 3 weeks; **doxorubicin (60 mg/m²) and cyclophosphamide (600 mg/m²), every 2 weeks. acupuncture, inhaled aromatherapy, and hypnosis, can help control anticipatory symptoms 9,10,[16][17][18][19] , which reinforces the role of psychological processes in the emergence of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The use of adjuvant therapies based on behavioral or psychological interventions, such as music therapy, mindfulness, RE: estrogen receptor; HER2: human epidermal growth factor receptor type 2; RE: estrogen receptor; HER2: human epidermal growth factor receptor type 2; *doxorubicin (60 mg/m²) and cyclophosphamide (600 mg/m²), every 3 weeks; **doxorubicin (60 mg/m²) and cyclophosphamide (600 mg/m²), every 2 weeks. acupuncture, inhaled aromatherapy, and hypnosis, can help control anticipatory symptoms 9,10,[16][17][18][19] , which reinforces the role of psychological processes in the emergence of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based interventions can effectively relieve stress, improve mental states including anxiety and depression, and improve the quality of life in breast cancer patients ( Kenne Sarenmalm et al, 2017 ; Priya and Kalra, 2018 ). Jing et al (2021) reported that mindfulness-based intervention improved overall outcomes among Chinese breast cancer patients. Recent research showed that a mindfulness-based stress reduction approach, group counseling, and survivorship education could reduce depressive symptoms in young breast cancer survivors ( Mirmahmoodi et al, 2020 ; Bower et al, 2021 ; Printz, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies believe that patients with higher levels of mindfulness can more quickly accept negative physical and mental problems during treatment, and form rational thinking patterns through "self-awareness" to relieve negative feelings. [27] It is suggested that clinical staffs can set up mindfulness cultivation programs to prevention the demoralization syndrome among cancer patients.…”
Section: Mindfulness Has a Negative Predictive Effect On Demoralizati...mentioning
confidence: 99%